Web Vibrations in Intraspecific Contests of Female Black Widow Spiders, Latrodectus hesperus. Issue 2 (2nd February 2023) - Krugner, Rodrigo; Espindola, Crystal; Justus, Nathan; Hatton, Ross L
Abstract: Female black widow spiders, Latrodectus hesperus Chamberlin and Ivie (Araneae: Theridiidae), are solitary predators of arthropods with no tolerance for intruders on the webs. In California, L. hesperus are found in urban and agricultural settings and can be a phytosanitary pest in fresh produce. Spatial separation of L. hesperus webs could be determined by seasonal population densities, with territorial competition expected under high densities in the environment. However, little is known about female-female communication behaviors in this species. In 1-hr laboratory observations, displays of female-female rivalry included production of vibrational signals in a majority (20 of 30) of trials. The number of signals produced by both females was highest during the initial 10 min of trials, with signaling rate (time interval between signals) peaking during the 40–50 min observation period. The overall ratio of signals produced by the resident female and the introduced female was about 5:1, with the number of signals produced by the resident female higher than the number of signals produced by the introduced female. Analysis of rivalry signals showed a peak in magnitude (about 0.4 m/s) ranging from 6 to 23 Hz and smaller peaks at about 29, 38, and 47 Hz. Collectively, these results demonstrate that female L. hesperus exhibit territorial rivalry and that female-female rivalry is mediated by emission of vibrational signals through the web. Understanding the mechanisms of intraspecific competition in L. hesperus is required for elucidating interspecific interactions in the environment and may lead to development of novel methods to prevent spiders from colonizing crops.